2018
DOI: 10.1200/jco.2018.79.2028
|View full text |Cite
|
Sign up to set email alerts
|

Double-Blind Phase III Trial of Adjuvant Chemotherapy With and Without Bevacizumab in Patients With Lymph Node–Positive and High-Risk Lymph Node–Negative Breast Cancer (E5103)

Abstract: Purpose Bevacizumab improves progression-free survival but not overall survival in patients with metastatic breast cancer. E5103 tested the effect of bevacizumab in the adjuvant setting in patients with human epidermal growth factor receptor 2-negative disease. Patients and Methods Patients were assigned 1:2:2 to receive placebo with doxorubicin and cyclophosphamide (AC) followed by weekly paclitaxel (arm A), bevacizumab only during AC and paclitaxel (arm B), or bevacizumab during AC and paclitaxel followed by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
48
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 58 publications
(49 citation statements)
references
References 63 publications
1
48
0
Order By: Relevance
“…Sparano et al (46) performed a per-protocol secondary analysis of the prospective NCT00433511 clinical trial, which accrued patients without clinical evidence of recurrence between 4.5 and 7.5 years after primary surgical treatment of HER2-negative stage II–III breast cancer followed by adjuvant systemic therapy (47). In this late recurrence substudy, the results indicated that 26 of 547 patients (4.8%, 95% CI = 3.1% to 6.9%) had positive CTC assay results.…”
Section: Follow-up Studiesmentioning
confidence: 99%
“…Sparano et al (46) performed a per-protocol secondary analysis of the prospective NCT00433511 clinical trial, which accrued patients without clinical evidence of recurrence between 4.5 and 7.5 years after primary surgical treatment of HER2-negative stage II–III breast cancer followed by adjuvant systemic therapy (47). In this late recurrence substudy, the results indicated that 26 of 547 patients (4.8%, 95% CI = 3.1% to 6.9%) had positive CTC assay results.…”
Section: Follow-up Studiesmentioning
confidence: 99%
“…[25][26][27][28][29][30] As in both colon cancer and NSCLC, bevacizumab was shown not to be of benefit in the adjuvant setting of breast cancer. 31,32 Other notable negative studies [33][34][35][36] It should be noted that despite the fact that most of the agents used in metastatic disease have been evaluated in the adjuvant setting, there are still approximately 20% of these agents that have yet to be studied for this purpose. The reasons for this are likely numerous and full consideration is beyond the scope of this discussion; however, this number suggests that there is still room for further exploration among existing agents.…”
Section: Jama Network Open | Oncologymentioning
confidence: 99%
“…Hence, angiogenesis is a key component of breast cancer growth, invasion and metastasis, and inhibition of angiogenesis has been an attractive strategy for breast cancer treatment, particularly using bevacizumab [12,13,15,16,18]. However, despite increased response rates in both the metastatic and neoadjuvant setting, bevacizumab has failed to show any overall survival benefit [64][65][66][67]. In addition, randomized clinical trials of dual therapy with bevacizumab and trastuzumab have not demonstrated an additional overall survival benefit of adding bevacizumab to trastuzumab and/or docetaxel chemotherapy despite some improvement in progression-free survival [11,12,16,17,19,20,68].…”
Section: Discussionmentioning
confidence: 99%